Landscape Structure Affects Bird Community in Bogor, West Java - Aronika Kaban; Ani Mardiastuti; Lilik Budi Prasetyo (Foresty Faculty of Hasanuddin University, 2018)
Birds have different responses to landscape modification, depends on its adaptation to the environment. The purposes of this study were to identify bird communities in several landscape types and to analyze the landscape structures that affect bird communities. The study was conducted from April to August 2016 at 29 landscapes in the city of Bogor. The landscapes were categorized into four types based on their fragmentation stages: intact, variegated, fragmented, and relict. Birds were surveyed using point count. Bird diversity was calculated using Shanon-Wienner Index, followed by Kruskal-Wallis statistical analysis, the similarity of communities was tested using Bray-Curtis. The landscape structures were quantified using 7 variables and measured using ArcGis patch analyst. Total 8,967 individuals from 75 species and 36 families were recorded. Similarity analysis of the bird community suggested that intact landscapes were clustered separately, while other three types were clustered together. The results showed that the abundance and species richness were higher in intact landscape. Bird diversity in Bogor becomes higher when the total edge, the mean shape index, and the shannon evenness index become smaller.